A cultural linguistic approach to friedrich holderlin’s poem bread and wine - Wang, Juan (American Journal of Social Sciences and Humanities, 2025)
Cultural linguistics examines discourse through integrating the culturally-defined, conventional, and contextually situated meaning with the dynamic, momentaneous, and emerging meaning. The poem of Friedrich Hölderlin engages themes such as divinity, homecoming, and the natural world, embodying great philosophical, poetic, and aesthetic value by manifesting the truth of human existential being. From a cultural-linguistic perspective, this paper aims to examine the application of cultural cognitive models in the meaning construction of Hölderlin’s poem Bread and Wine. We first introduced the development of cultural linguistics and its integration into cognitive linguistics theories, and then identified and analyzed four major cognitive models: the propositional model, image-schematic model, metaphoric model, and metonymic model manifested in the poem within the cultural contexts, exploring how they contribute to the poetic meaning construction process. The findings of this paper show that the poetic discourse's meaning is greatly shaped by human cognitive structures and cultural contexts, and different cognitive models rooted in the poet’s embodied experience with the surrounding environment govern the meaning construction process and demonstrate the core poetic themes of humanity, spirituality, and divinity. This study may provide readers with both cognitive and cultural pathways into poetic discourse interpretations. Further research is expected to explore a more comprehensive cultural linguistic model that governs the meaning construction of poetic discourses.